1996
DOI: 10.1021/je9502096
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of Difluoromethane and Pentafluoroethane along the Saturation Line

Abstract: The paper reports new measurements of the viscosity of liquid difluoromethane (HFC-32) over the temperature range 233.15 K to 333.15 K and the viscosity of pentafluoroethane (HFC-125) over the temperature range 233.15 K to 328.15 K along the saturation line. The viscosities were measured in a calibrated capillary viscometer. A new method was developed to operate the viscometer and to analyze the measured data. The uncertainty of the results is estimated to be no more than 3%. The results were correlated as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Han et al [ 9 ] enclosed a straight glass capillary viscometer according to Ostwald in a stainless steel pressure vessel with windows through which the efflux of the test sample through the capillary could be observed and timed. Their measurement results for the viscosity of hydrofluorocarbon 1,1,1,2-tetrafluoroethane (R134a) as well as those obtained with this instrument by Sun et al [ 10 ] for difluoromethane (R32) and pentafluoroethane (R125) showed systematic deviations from literature data.…”
Section: Introductionmentioning
confidence: 73%
“…Han et al [ 9 ] enclosed a straight glass capillary viscometer according to Ostwald in a stainless steel pressure vessel with windows through which the efflux of the test sample through the capillary could be observed and timed. Their measurement results for the viscosity of hydrofluorocarbon 1,1,1,2-tetrafluoroethane (R134a) as well as those obtained with this instrument by Sun et al [ 10 ] for difluoromethane (R32) and pentafluoroethane (R125) showed systematic deviations from literature data.…”
Section: Introductionmentioning
confidence: 73%
“…Liquid kinematic viscosity for R32 under saturated condition from SLS in comparison with literature data: ■, this work; – , the fitting equation with eq ; ○, ref ; ◁, ref ; ▷, ref , ◇, ref ; ▽, ref ; △, ref .…”
Section: Resultsmentioning
confidence: 94%
“…Figure represents the deviations of the experimental viscosity data for R32 and literature data are also included for comparisons. Laesecke et al, Sun et al, and Ripple et al measured the viscosity of R32 by a capillary viscometer with a stated uncertainty of 2.4, 3, and 5%, respectively. Their data agree well with our results with the maximum deviation of 3.05, 5.13, and 2%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Given these data, Equation (12) can be solved for the unknown . In this way, a local scaling factor is et al (1979), 15*Dymond and Young (1980), 16*Medani and Hasan (1977), 17*Rasulov (1994), 18*Agaev and Golubev (1963), 19*Tanaka et al (1991), 20*Carmichael et al (1969), 21*Rastorguyev and Keramidi (1974), 22*Assael and Polimatidou (1994), 23*Diller et al (1993), 24*Arnemann and Kruse (1991), 25*Phillips and Murphy (1979, 26* Kumagai and Takahashi (1991), 27*Takahashi et al (1987), 28*Mayinger (1991), 29, Ripple and Matar (1993), 30*Okubo and Nagashima (1993), 31*Nabizadeh and Mayinger (1992, 32 ), 33*Diller and Peterson (1993), 34*Oliveira and Wakeham (1993a, 35*Li-Qun Sun et al (1996), 36*Heide (1996, 37 *Wilson et al (1992), 38 , 39*Kuma gai and Takahashi (1993), 40*Laesecke andDe"baugh (1996). * Phase: l"liquid, v"vapour, sc"supercritical, sl"saturated liquid; sv"saturated vapour.…”
Section: Local Dexnition Ofmentioning
confidence: 99%
“…Saturated liquid experimental viscosity data for R125. (*) Sun et al (1996); (᭹) Oliveira and Wakeham (1993a); ( ) Wilson et al (1992); (£) Heide (1996); () .…”
Section: The Proposed Modelmentioning
confidence: 99%